Fixed combination vs. generic – BE without dilemmas - Pejčić, Zorica; Nikolić, Snježana; Neđić, Tanja (Archives of Pharmacy, 2022)
Clinical development of a fixed combination should correspond to the intended claim. Particular attention should be given to the doses of each active substance in the fixed combination medicinal product, with each dose combination being scientifically justified and clinically relevant. The aim of this paper is to systematically present the clinical development of fixed combinations, the difference between fixed combinations and generic drugs containing two or more active substances, as well as the justification for biowaiver for additional strengths, which are the most common dilemmas during drug development and assessment of clinical documentation. For the fixed combination application, complete clinical documentation is submitted. Three therapeutic scenarios with gradually increasing complexity of clinical data have been defined:Substitution therapy in patients adequately controlled with two or more active substances used in combination - most common in practiceAdd-on treatment of patients insufficiently responding to an existing therapy with one or more active substances,Initial combination therapy for patients receiving previously neither of the substances.Clinical development of a fixed combination should support the rationale for combined use of the active substances. The presence or absence of a pharmacokinetic interaction between the active substances in the fixed combination medicinal product should be established. In a bioequivalence study for a fixed combination, the tested drug is compared with two simultaneously applied reference drugs. The development of a generic medicinal product containing two or more active substances is based on demostrating bioequivalence with  reference fixed combination medicinal product.